2022
DOI: 10.1002/anie.202117843
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Tunable Chiral 2,2′‐Bipyridine Ligands: Application to the Enantioselective Nickel‐Catalyzed Reductive Arylation of Aldehydes

Abstract: A new class of chiral 2,2'-bipyridine ligands, SBpy, featuring minimized short-range steric hindrance and structural tunability was rationally designed and developed, and the effectiveness was demonstrated in the first highly enantioselective Ni-catalyzed addition of aryl halides to aldehydes. In comparison with known approaches using preformed aryl metallic reagents, this reaction is more step-economical and functional group tolerant. The reaction mechanism and a model of stereocontrol were proposed based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 85 publications
0
30
0
Order By: Relevance
“…To embark on the investigation, 2‐chloro‐3,4‐dimethoxybenzaldehyde ( 1 ) was chosen as the model substrate (Table 1). The SBpy‐type chiral ligands L1 ‐ L4 were prepared based on our previous synthetic route [18a–c] . After extensive experimentation, a set of “standard conditions” was established in which the desired reductive coupling product 2 could be produced in 92 % yield and 95 : 5 er.…”
Section: Resultsmentioning
confidence: 99%
“…To embark on the investigation, 2‐chloro‐3,4‐dimethoxybenzaldehyde ( 1 ) was chosen as the model substrate (Table 1). The SBpy‐type chiral ligands L1 ‐ L4 were prepared based on our previous synthetic route [18a–c] . After extensive experimentation, a set of “standard conditions” was established in which the desired reductive coupling product 2 could be produced in 92 % yield and 95 : 5 er.…”
Section: Resultsmentioning
confidence: 99%
“…Further mechanistic investigation revealed that the migratory insertion of the aldehyde into an aryl cobalt species was the rate-determining step of the reductive addition reaction. We believe this work represents a new and sustainable avenue for the rapid construction of highly significant chiral benzyl alcohols …”
Section: Discussionmentioning
confidence: 97%
“…Chemie medium gave slightly lower er value in comparison with the ternary system and for the latter two solvents, the yield was also significantly lower (entries [14][15][16].…”
Section: Methodsmentioning
confidence: 99%